Improving students' critical thinking skills through the CTL learning model in fiqh subjects at Madrasah Aliyah Darus Sholihin - Siti Wahyuni Dhofir; Nur Laila Maulidiyah; M Andika; Abdul Muhaimin Akhmadi; Maulid Agustin (Journal of Loomingulisus ja Innovatsioon, 2024)
This study aims to evaluate the effectiveness of the Contextual Teaching and Learning (CTL) model in enhancing students' critical thinking skills in the subject of Fiqh, specifically focusing on the topics of zakat, infaq, and sadaqah, among tenth-grade students at MA Darus Sholihin Probolinggo. The research is grounded in the importance of critical thinking skills for students to understand and apply Islamic teachings contextually in their daily lives. Conducted as Classroom Action Research (CAR), this study involved nine tenth-grade students, with data collection through observation, documentation, and tests validated using triangulation techniques. Findings reveal that the gradual implementation of CTL in Cycle I and Cycle II significantly improved student engagement and critical thinking in Fiqh. By Cycle II, over 88% of students achieved mastery, indicating that CTL is effective in helping students connect their learning with real-life contexts. This research is anticipated to contribute to the development of more relevant Islamic education systems that foster critical thinking skills among students in Islamic boarding schools.